The differentiated workforce : transforming talent into strategic impact - Becker, Brian E. (Harvard Business Press, 2009)
In 'The Differentiated Workforce', the authors expand on their previous books, 'The HR Scorecard' and 'The Workforce Scorecard', and recommend that you manage your workforce like a portfolio - with disproportionate investments in the jobs that create the most wealth.